Analysis methodology and design verification for strengthening moment-resisting caisson foundations. (15th March 2023) - Guner, Serhan
Highlights: A well-defined analysis methodology for the system-level structural design verification. It quantifies the load, deformation, cracking, and failure response both at the SLS and ULS. It encourages better reinforcement detailing and facilitates iterative design improvements. Valid and efficient analysis models presented are suitable for the use of engineers. Proposed methodology is independent of the computer program used. Abstract: Many existing monopole towers rely on caisson foundations to resist the effects of large overturning moments. Increased loading on these towers, coupled with material deterioration and more stringent code requirements, often results in the overloading of the existing caissons. The strengthening of these caissons for additional overturning resistance presents many challenges and typically requires the installation of new piles. A pile cap is commonly used to connect the existing caisson to the new piles. The proper design of the pile cap has a critical importance in ensuring an effective stress transfer and creating a resilient foundation system. While a number of strengthening design approaches are repeatedly used in industry, there is a dearth of guidance and proven analysis methods to verify the performance achieved with these approaches. This study proposes a well-defined analysis methodology for the system-level structural design verification of the strengthened foundation systems. The methodology provides two routes, using either the strut-and-tie or nonlinear finite element analysis methods, to quantify the load, deformation, cracking, and failure responses. The methodology helps expose and address the weak aspects of the design using an iterative design improvement process. A common strengthening design approach from industry, involving a moment-resisting caisson strengthened with four concrete piles and a pile cap, is used as a case study to demonstrate the application of the methodology. The results demonstrate that the methodology provides significant insight into the system-level behavior both at the serviceability and ultimate limit states. The analysis results are found useful in identifying the locations where modified bar detailing could significantly improve the system performance. The improved design from the methodology provided a 56 % increase in the load capacity for the case-study foundation while still using the same amounts of reinforcing steel and concrete as compared to the initial design before the application of the proposed methodology. This paper presents the studies undertaken, conclusions reached, and recommendations made for developing resilient pile cap designs for strengthening moment-resisting caisson foundations.